Antipyretic Activity Test of Combination of Peperomia pellucida Extract and Andrographis paniculata in Mice (Mus musculus) - Khairil Pahmi; Muhammad Ricky Ramadhian; Gabena Indrayani Dalimunthe (Jurusan Farmasi Universitas Negeri Gorontalo, 2022)
Pepper elder (Peperomia pellucida) and green chiretta (Andrographis paniculata) are plants that have been used empirically to reduce fever. Fever is a symptom of a disease characterized by a significant increase in body temperature. This study aimed to determine the antipyretic effect of the combination of pepper elder herbal extract (P. pellucida) and green chiretta herbal extract (A. paniculata) (80:20) in the male house mice (Mus musculus). Extraction was conducted through maceration using ethyl acetate solvent. The total of 25 male mice were divided into 5 groups, namely a negative control group (Na-CMC 1%), a positive control group (paracetamol), and a treatment group induced by a combination of pepper elder herbal extracts and green chiretta herbal extract at the dose of (80 + 20), (40 +10), and (20 + 5) mg/kg BW. DPT vaccine 0.2 ml was used intramuscularly as a fever inducer. The observation was carried out at 30, 60, 90, and 120 minutes after treatment. The data obtained were analyzed using one-way ANOVA followed by the LSD test to determine the differences between groups. The results showed that variations in the dose of the combination of pepper elder and green chiretta herbal extracts had an antipyretic effect where the most effective dose was (80 + 20) mg/kg BW due to its stable temperature reduction power and effectiveness that are equivalent to paracetamol. The combination of suruhan herb extract (P. pellucida) and sambiloto herb (A. paniculata) has potential as an antipyretic